Impact of diabetes mellitus on lymphocyte GRK2 protein levels in patients with heart failure. (February 2015) - Rengo, Giuseppe; Pagano, Gennaro; Paolillo, Stefania; de Lucia, Claudio; Femminella, Grazia D.; Liccardo, Daniela; Cannavo, Alessandro; Formisano, Roberto; Petraglia, Laura; Komici, Klara; Rengo, Franco; Trimarco, Bruno; et al.
Abstract Background Diabetes mellitus (DM) is associated with impaired prognosis in patients with heart failure (HF), but pathogenic mechanisms are unclear. In the failing heart, elevated β‐adrenergic receptor (β‐AR) activation by catecholamines causes G‐protein‐coupled receptor kinase‐2 (GRK2) upregulation which is responsible for β‐AR signalling dysfunction. Importantly, GRK2 expression, measured in peripheral lymphocytes of HF patients, correlates with levels of this kinase in the failing myocardium reflecting the loss of hemodynamic function. Moreover, HF‐related GRK2 protein overexpression promotes insulin resistance by interfering with insulin signalling. The aim of this study was to assess lymphocyte GRK2 protein levels in HF patients with and without DM. Methods and materials Patients with a diagnosis of HF were enrolled in the study. All subjects underwent a complete clinical examination (including NYHA functional class assessment and echocardiography) and blood draw for serum N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), lymphocyte GRK2 and plasma norepinephrine (NE) levels. Demographic data including age, sex, medications, cardiovascular risk factors and presence of comorbidities were also collected. Results Two hundred and sixty‐eight patients with HF (left ventricular ejection fraction [LVEF] 30·6 ± 7·6%) with and without DM were enrolled. No differences between the two groups were found in terms of demography, HF aetiology, LVEF, NYHA class, NE and NT‐proBNP. GRK2 was significantly higher in patients with DM compared to non‐DM. At multivariate linear regression analysis, LVEF, NE, NT‐proBNP and diabetes came out to be independent predictors of GRK2 levels in the overall study population. Conclusion In HF patients, DM is associated with significantly more elevated lymphocyte GRK2 protein levels, likely reflecting more compromised cardiac β‐AR signalling/function, despite similar hemodynamic status and neuro‐hormonal activation compared to patients without DM. These findings contribute to explain the negative prognostic impact of DM in patients with HF.